Megalithic Heritage Of Traditional Villages In Ende - Wati, Fatma; Bela, Elisabeth Susanti (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Flores Island, especially Ende Regency, has abundant potential and wealth of archaeological heritage which is still preserved today. The potential of these cultural resources should be maintained and preserved in various forms, one of which is through research and scientific publications so that they are better known by today's modern society. This research, which is included in qualitative descriptive research, uses research strategies in the Wolotopo Traditional Village and Kozibari Traditional Village in Ende Regency, making the process of data collection and data analysis easier. The open interview technique allows informants to have more freedom in providing answers so that general macro conclusions can be drawn. Literature studies and presentation of research documentation can strengthen descriptions and narratives of informal presentations. The research results show that various megalithic remains in the traditional village residential area in Ende are still well preserved and are still used in various traditional rituals.